ANALYSIS OF THE AREA TYPES OF SCUTELLARIA SPECIES DISTRIBUTED IN THE FLORA OF THE FERGANA VALLEY (Scientific journal of the Fergana State University, 2024)
This article presents the analysis of scientific research conducted to determine the geography and area types of Scutellaria species from the Lamiaceae family distributed in the Fergana Valley. In conducting the analysis of the area types of the species, classical publications on local floras in Central Asia, as well as recent publications, were utilized.According to the research results, the natural distribution boundaries of the Scutellaria species found in the valley flora were identified, and they were classified into 11 area types. These area types were further divided into four area classes: Western Tian Shan (7), Pamir-Alai (5), Middle Asian Mountains (10), and Paleoarctic (1). Out of the 23 species of the Scutellaria genus in the valley flora, 22 (96%) are considered endemics of Central Asia, recognized as centers of local species formation.